2017
DOI: 10.1371/journal.pone.0176548
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of formal care use and expenses among in-home elderly in Jing’an district, Shanghai, China

Abstract: The need for formal care among the elderly population has been increasing due to their greater longevity and the evolution of family structure. We examined the determinants of the use and expenses of formal care among in-home elderly adults in Shanghai. A two-part model based on the data from the Shanghai Long-Term Care Needs Assessment Questionnaire was applied. A total of 8428 participants responded in 2014 and 7100 were followed up in 2015. The determinants of the probability of using formal care were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 34 publications
4
20
0
1
Order By: Relevance
“…Consistent with the prediction of Anderson's behavioural model and evidence from the US and European countries, this study shows that both self‐reported needs and functional limitations are important predictors of care receipt in China. This also concurs with the evidence reported in a previous study conducted in the Jing'an District of Shanghai, China (Li et al, ). Perceived proximity of care is found to be the most important predictor of care use, with its effect size being much higher than that of other predictors.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with the prediction of Anderson's behavioural model and evidence from the US and European countries, this study shows that both self‐reported needs and functional limitations are important predictors of care receipt in China. This also concurs with the evidence reported in a previous study conducted in the Jing'an District of Shanghai, China (Li et al, ). Perceived proximity of care is found to be the most important predictor of care use, with its effect size being much higher than that of other predictors.…”
Section: Discussionsupporting
confidence: 93%
“…Older people in the higher age bands and reporting IADL or ADL disabilities are more likely to receive financial support from the government rather than paying for services themselves. of Shanghai, China (Li et al, 2017). Perceived proximity of care is found to be the most important predictor of care use, with its effect size being much higher than that of other predictors.…”
Section: Independent Variablesmentioning
confidence: 86%
See 1 more Smart Citation
“…When applying Andersen's model to home care use, the preeminence of need factors was obvious. The association with limitations in ADL/IADL has already been extensively established and, in our case, was further strengthened by taking into account their evolution over the study period [7,8,[17][18][19][20][21][22][23]. In a logistic regression model including this variable, the number of other need factors remaining significantly associated with home care utilization was actually limited.…”
Section: Discussionmentioning
confidence: 70%
“…It would appear that only one study (Simon, Kumar, & Kendrick, 2008) The predictors of stroke survivors' formal and informal caregiving needs are still unknown. Studies on other patient populations, such as patients with dementia and those of advanced age, have indicated that higher numbers of hours of formal and informal care are associated with greater disease severity, increases in behavioural problems, increased difficulties in performing the ADL (Bakker et al, 2013), older age, female gender, not having a spouse, higher income, and presence of stroke or dementia (Li et al, 2017;Rogero-Garcia, 2009). To date, the formal and informal care received by stroke survivors during the first year of home discharge has not been precisely quantified.…”
Section: Backg Rou N Dmentioning
confidence: 99%